Breathing dystonia in Meige syndrome. (2021) - Watson, Natalie Anne; Hicklin, Lucy Anne; Marion, Marie-Helene
Highlights: 13 patients with Meige (craniocervical dystonia) syndrome and breathing difficulties were identified, 6 with and 7 without laryngeal involvement. 77% had a good (>50%) response to Botulinum toxin injection(s). Among the 13 Meige patients, all patients, except one, had clinical signs of supra-hyoid muscles involvement, we believe this muscle group is the main cause of the dyspnoea in this specific Meige phenotype. Abstract: Background: Dyspnoea is rarely mentioned in the clinical description of adult-onset isolated dystonia. In this study, we present the clinical features of 13 patients with Meige syndrome (cranio-cervical dystonia) with breathing difficulties. Methods: A retrospective case note review was performed of patients presenting with Meige syndrome and shortness of breath, to a neuro-laryngology MDT clinic. Results: Some patients were severely limited by their breathlessness, but others did not volunteer these symptoms. The majority of patients were referred with the assumption that the larynx was the cause of the problem; however half the patients did not have evidence of laryngeal involvement. Of the patients who had laryngeal involvement, injecting the larynx alone did not always relieve the dyspnoea. The majority of our patients responded to injection of the suprahyoid muscles, including genioglossus, digastric and mylohyoid. Conclusion: We recommend routinely establishing if the patient with Meige syndrome has signs or symptoms of breathlessness, and establishing the level of the problem, as this can be treated successfully.